Adsorptive denitrogenation of model oil by MOF(Al)@GO composites: remarkable adsorption capacity and high selectivity. (23rd January 2023) - Hu, Xin; Zuhra, Zareen; Ali, Shafqat; Zhou, Yunshan; Zhang, Lijuan; Duan, Xiaoya; Zhao, Zipeng
Abstract : An as-synthesized recyclable Al-NDC@GO composite exhibited remarkable adsorption capacity and high selectivity for pyridine, quinoline and indole. Abstract : Al-NDC@GO composites were hydrothermally prepared via a single step in situ synthesis through the reaction of 1, 4-naphthalene dicarboxylic acid (1, 4-H2 NDC), Al(NO3 )3 ·9H2 O in H2 O with graphene oxide (GO), and characterized well using various analytical techniques. The experimental results showed that Al-NDC@GO with optimal GO loading exhibited remarkable adsorption capacity for the liquid phase adsorption of pyridine, quinoline and indole in oil in the order of quinoline (670 mg quinoline per g) > pyridine (533 mg pyridine per g) > indole (487 mg indole per g), high adsorptive selectivity in the presence of naphthalene and benzene, and satisfactory recyclability. The mechanism behind this excellent adsorption of NCCs is thought to be due to the high surface area, porosity, and the presence of unsaturated metal sites and excessive oxygen groups on exfoliated layers of GO sheets, especially those that are not involved in bonding with Al-NDC moieties, because all these factors may be involved in the interaction of the composites and the nitrogen-containing compounds.